Mood and mental health of Peruvian dentists during the COVID-19 pandemic - Bladimir Domingo Becerra Canales; Marcos Rubén Calle Quispe; Ángela Silvia Condori Becerra (Editorial Ciencias Médicas, 2021)
Introduction: The COVID-19 pandemic may alter the mood and mental health of dentists. It may likewise affect the well-being of professionals and create disorders that will influence their lives. Objective: Describe the moods and mental health of Peruvian dentists during the COVID-19 pandemic. Methods: A cross-sectional longitudinal descriptive study was conducted in a region of Peru from April to June 2020, with the participation of 336 dentists from public health institutions and private consultation offices. Social and professional data were collected. Use was made of the Mood Assessment Scale and Goldberg's General Health Questionnaire. The study variables were described and differences were evaluated with the chi-squared test. Results: Of the total participants, 53.6% were female; 56.8% were married / cohabited with their partners; 70.8% were Catholic; 39.9% had 5-15 years' professional experience, and 53.6% were from private consultation offices. In terms of mood, 47.6% were anxious, 33.0% were hostile and 38.4% were depressed; 66.7% had bad mental health; 63.1% had general dysphoria and 81.0% were socially dysfunctional. Conclusions: During the COVID-19 pandemic it was common for Peruvian dentists to present negative moods such as anxiety, depression and hostility. A high prevalence was also found of bad mental health, general dysphoria and social dysfunction.